The effect of managerial ownership, profitability and leverage on earnings management in islamic economic perspective - Yulinda, Tika; Sari, Yetri Martika; Ermawati, Liya (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The emergence of earnings management is the impact of agency problems that occur between the owners and management of the company caused by a misalignment of interests and is often referred to as agency conflict. This earnings management action can reduce the credibility of financial reports because the figures presented in the financial reports do not reflect the actual situation. This study aims to analyze partially and simultaneously the effect of managerial ownership, profitability and leverage on earnings management in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2023 period. This research is a quantitative study. The type of data used is secondary data obtained from the company's official website on the Indonesia Stock Exchange. The sample in this study consisted of 12 companies in the 2020-2023 period, totaling 48 sample data. The data analysis used is panel data regression analysis using the E-Views 9 program. The results of this study indicate that partially managerial ownership and profitability do not affect earnings management, while leverage has a positive and significant effect on earnings management. Simultaneously managerial ownership, profitability and leverage affect earnings management.